Implementation of Islamic Bank Loss Sharing in Completing Write Off Account on Bank Assets (Study at PT Bank Mega Syariah KC Jambi) - Rahman Arifin; Muhammad Istan; Mega Ilhamiwati; Ahmad Danu Syaputra (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: Altogether, this study seeks to decrease the gaps left by previous studies that did not address the default policy on the risk of non-performing financing. The purpose of this research is to learn about the process of write off (WO) account settlement in Islamic Banking as well as the loss sharing policy at PT. Bank Mega Syariah.Design/Method/Approach: The researcher utilized a qualitative descriptive approach in this study. This approach is used because the researcher requires only information, explanations, and oral information to compile this research. The data were collected through observation and direct interviews with the research object and documentation.Findings: It can be concluded that there are many stages and processes in the settlement of Write Off (WO) accounts at Bank Mega Syariah KC (Ind. Kantor Cabang, Brach Office) Jambi, including Partial Payments, Gradual Payments, Full Payments, Auctions, Voluntary Guarantees Sales, and through Religious Courts/Local Courts. Bank Mega Syariah hopes that the settlement process can be carried out through Voluntary Guarantee Sale (Ind. Jual Jaminan Sukarela - JJSR) rather than auction or other media. The bank also does not anticipate using auction media in the settlement process because, in addition to being difficult to find potential buyers, the price offered is not in line with what customers expect. Cut Loss policy or cuts below the main outstanding is a policy offered by Bank Mega Syariah to assist in goodness. One of them offers a repayment discount that is less than the outstanding principal (Cut Loss). In addition to being given a discount below the outstanding principal, Bank Mega Syariah KC Jambi also provides easy returns for customers who wish to pay off debts. Repayments that have been approved by the Board of Directors can be paid off in stages within period of 3 (three) months since the approval of the proposed Gradual Cut Loss Memorandum.Originality/Values: The researcher hopes that the findings of this study can help to decrease the gaps left by previous studies that did not address the default policy on the risk of non-performing financing and will help banks make decisions that are mutually lenient.